Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills - Bernard, Ernest C. (Zootaxa, 2016)
Two new genera and five new species of Tullbergiidae (Collembola) are described from the North American Appalachian zone in eastern Tennessee and western North Carolina. Ameritulla n. gen. is established for species with 15 setae on the middle tibiotarsus, blunt papilla A on the labial palpus, two long rows of vesicles in the postantennal organ (PAO), two dorsal sensilla on the third antennal segment and crescentic pseudocelli. Ameritulla clavata (Mills, 1934) n. comb. (=Tullbergia clavata Mills, 1934) is designated as type species and redescribed from type specimens, and A. obscura n. sp. is described. On Mixturatulla ozwini n. gen., n. sp. papillae A and B of the labial palpus are thick and blunt, the second row of the PAO is laterally broken into numerous spherical vesicles, and the dorsum of Abd. VI has two rows of large, coalesced tubercles. Psammophorura miniclavata n. sp. lacks pseudocelli on the third abdominal segment, which are present in previously described species. Stenaphorura shaconage n. sp. is the first species of its genus reliably recorded from North America. It differs from its Palaearctic relatives in having 2+2 pseudocelli on most body segments. Tullbergia nearctica n. sp. resembles T. arctica (Wahlgren, 1900) but differs in several chaetotaxic characters. Sensilliform setae traditionally considered as ordinary pointed setae are recognized and charted. A new setal nomenclature is proposed for the ventral setae of the sixth abdominal segment.